Analisis dimensi proses kognitif pada soal formatif dalam buku bahasa indonesia aku bisa kelas 1 sekolah dasar - Sayekti Uji Harini; Sukarno Sukarno; Siti Wahyuningsih (Didaktika Dwija Indria, 2023)
This study aims to describe and analyze the distribution of cognitive process dimensions in formative questions in the Indonesian language book "Aku bisa!" grade 1 elementary school merdeka curriculum. This research is a type of content analysis research with a descriptive qualitative approach. The research data is in the form of a distribution of formative assessment questions categorized according to the cognitive levels of Bloom revised by Anderson and Krathwohl. The data analysis technique used Creswell's spiral analysis model. The results of this study showed that Indonesian formative assessment questions were found to be unevenly distributed and integrated in the learning process. This has the benefit of providing feedback for students regarding mastery of learning materials and feedback for teachers to improve and perfect further learning. The formative assessment questions in the grade 1 Indonesian book "Aku Bisa!" cover six cognitive dimensions with a distribution of C1 50%, C2 27%, C3 3%, C4 10%, C5 7%, and C6 3%. Basically, grade 1 students are still in the beginning reading and writing stage. However, they also need to be trained to develop their thinking skills through language activities.